Development of Solar Power Plant to Support Smart Farming 4.0 at Hubbul Khoir Islamic Boarding School Indonesia - Sutrisno W. Ibrahim; Muhammad Nizam; Agus Ramelan; Adriel Satrio Nugroho; Salsabila Putri (Universitas Sebelas Maret (UNS), 2023)
Electricity is a very crucial thing in human life today such as for communications, education, offices, household appliances, and transportation. Unfortunately, most of the electricity in Indonesia is still generated by fossil fuels such as coal. Indonesia which is on the equator has an advantage in solar power generation. Every area in Indonesia gets sunlight for a full year. In this paper, we develop a 1.62 kWp solar power plant at the Hubbul Khoir Islamic Boarding School Indonesia. Energy generated from solar panels is used to support the hydroponic farming system owned by the Islamic boarding school. Economic analysis is used to find out whether the installed generating system is profitable or not. Power quality analysis is used to determine whether the load can be supplied with good power quality. The results obtained by the monitoring system can monitor the PV output power and the power to the load with a display on the LCD screen and on the web with overall accuracy above 96%, economic analysis results show that the system will return on investment after 6.8 years with a profit in the 25th year of Rp20,871,282, and quality the power in this system has good power quality from the PLN side and the inverter side.